Probabilistic Inferences Under Emotional Stress: How Arousal Affects Decision Processes. (27th August 2015) - Wichary, Szymon; Mata, Rui; Rieskamp, Jörg
Abstract: Many models of decision making neglect emotional states that could affect individuals' cognitive processes. The present work explores the effect of emotional stress on people's cognitive processes when making probabilistic inferences. Two contrasting hypotheses are tested against one another: the uncertainty‐reduction and attention‐narrowing hypotheses of how emotional stress affects decision making. In the experimental study, emotional stress was induced through the use of highly aversive pictures immediately before each decision. Emotional state was assessed by both subjective (state anxiety, arousal, and pleasantness ratings) and objective (skin conductance) measures. The results show that emotional stress impacts decision making; in particular, emotionally aroused participants seem to have focused on the most important information and selected simpler decision strategies relative to participants in a control condition. The results are in line with the attention‐narrowing hypothesis and suggest that emotional stress can impact decision making through limited predecisional information search and the selection of simpler decision strategies. Copyright © 2015 John Wiley & Sons, Ltd.